Trustworthiness judgments and Borderline Personality Disorder: an experimental study on the interplay of happiness and trustworthiness appraisals and the effects of wearing face masks during the Covid-19 pandemic in Germany - Biermann, Miriam; Schulze, Anna; Unterseher, Franziska; Hamm, Marie; Atanasova, Konstantina; Stahlberg, Dagmar; Lis, Stefanie (Borderline Personality Disorder and Emotion Dysregulation, 2022)
Judging positive emotional states or the trustworthiness of others is important for forming and maintaining social affiliations. Past studies have described alterations in these appraisal processes in Borderline Personality Disorder (BPD), which might have been exacerbated during the Covid-19 pandemic by the requirement to wear face masks. In the present study, we investigated in an online-survey a) whether social judgments are particularly strongly affected in individuals with BPD when they have to judge happiness and trustworthiness in facial stimuli covered by a mask, b) whether appraising a positive emotional state affects trustworthiness appraisals differentially in BPD and healthy individuals and c) whether social judgments are related to how individuals with BPD experience wearing masks during the pandemic.